Artificial intelligence-produced radiographic enhancements in dental clinical care: provider and patient perspectives - Slashcheva, Lyubov D.; Schroeder, Kelly; Heaton, Lisa J.; Cheung, Hannah J.; Prosa, Brenda; Ferrian, Nicole; Grantz, Jesse; Jacobi, Deborah; O’Malley, John J.; Helgeson, Michael; Tranby, Eric P. (Frontiers in Oral Health, 2025)
IntroductionArtificial intelligence (AI)-based software can be used with dental radiographs to facilitate dental providers’ diagnoses and to educate patients about their oral health conditions. The goal of this study was to survey dental providers and patients about the use of AI-enhanced radiographs in the diagnostic and patient education processes.MethodsWithin their Community Collaborative Practice model, Apple Tree Dental in Minnesota implemented the use of an AI software platform that annotates carious lesions and periodontal measurements on dental radiographs. Before and after implementation of this software, providers (dentists, dental hygienists, dental therapists, and dental assistants) were surveyed about what benefits and challenges they anticipated and experienced in using the AI software. A small-scale study of patients who viewed AI-generated annotations on their own radiographs examined patient perspectives on the use of this software.ResultsDental therapists reported using the software most often, with 57.2% using the software at least 50% of their clinical time; 79% of dental assistants reported using the software 25% of the time or less. While the majority of providers (n = 70 for Survey I; n = 53 for Survey II) said that AI enhancements would help facilitate patient education efforts, providers’ confidence in the ability of the AI software to improve diagnosis of dental caries and periodontal disease and its ability to improve the efficiency of their work was mixed. Patients (n = 25) found reviewing the AI-produced visual aids used by their dental provider to be helpful in understanding their oral health, and a large proportion (92%) said they planned to follow through on recommended treatment.DiscussionWhile provider and patient perceptions of the use of AI software in dental care were positive overall, attitudes among providers were mixed regarding its effectiveness in diagnosing dental disease and improving work efficiency. More research is needed to determine whether use of AI software in clinical dental practice produces changes in treatment recommendations by providers or in patient adherence to these recommendations.